Women’s Understanding of ICT at Coastal Area - Amiruddin Saleh; Susri Adeni; Aida Vitayala Hubeis; Arif Satria (Journal of Management Practices, Humanities and Social Sciences, 2018)
This study aims to explore the understanding of women in coastal area in Indonesia especially in Sukabumi, West Java province about the internet. Information, Communication and Technology (ICT) has rapidly growth in Indonesia, specifically the use of internet has increased drastically. A huge number of people have been utilizing internet in Indonesia including the Indonesian coastal areas. Thus, it is interesting to observe and investigate the role of internet in improving people's lives especially women in coastal areas. Also, there is a lack of study on how women at coastal area “see” the internet. Qualitative research method is applied in this study based on observation and interview. Respondents were the women from coastal areas. The results show that most of women have a sophisticated mobile phone, but they sometimes do not know about its applications. Thus, the internet is remained abandoned and women do not use the internet in order to have information. Further to this, most of their children know how to use the internet such as to play the game and to use social media such as facebook, instagram and whatsapp. This study would provide insights to local government and policy makers so that they may enforce the women to utilize the internet and let the society become media literate.